Validation of an Information Justice Model in Iran’s Public Education System - Ebneshahidi , Zohrehalsadat; Shahtalebi, Badri; Nadi Khorasgani, Mohammad Ali (Assessment and Practice in Educational Sciences, 2026)
This study aimed to develop and validate a comprehensive model of information justice for Iran’s public education system using a mixed-methods exploratory–confirmatory approach. This research employed a sequential mixed-methods design consisting of a grounded theory phase followed by a quantitative validation phase. In the qualitative stage, in-depth semi-structured interviews were conducted with 35 experts, principals, educational administrators, and university faculty using purposive and theoretical sampling until theoretical saturation was achieved. Data were analyzed using open, axial, and selective coding based on the Strauss and Corbin systematic approach, resulting in the identification of causal, contextual, intervening, strategic, and outcome conditions within a paradigm model. In the quantitative stage, a researcher-made questionnaire derived from qualitative findings was administered to a multi-stage probability sample of 390 principals and educational experts across five provinces, yielding 381 usable responses. Content validity was assessed using the CVR method, and reliability was evaluated through internal consistency indices. Confirmatory factor analysis and structural equation modeling were applied to assess the factorial structure and test the overall model fit. Confirmatory factor analysis demonstrated that all primary constructs of the information justice model achieved acceptable or strong standardized factor loadings. Model fit indices for all dimensions—including IFI, CFI, TLI, NFI, RMSEA, and χ²/df—fell within acceptable thresholds, indicating robust factorial validity. Structural relationships among causal conditions, contextual factors, intervening conditions, strategies, and outcomes were statistically significant, confirming the internal coherence of the theoretical model. The final model showed strong predictive power for key organizational outcomes such as reduced polarization, enhanced self-efficacy, and increased strategic alignment. The validated model offers a theoretically grounded and empirically supported framework for analyzing and promoting information justice within Iran’s public education system, demonstrating that organizational structures, cultural conditions, and ethical strategies collectively shape equitable information governance.